Parental response to intruder females altered by ornamentation and mate quality in a biparental fish. (4th April 2018) - Robart, Ashley R; Sinervo, Barry
Abstract : Parents jointly defend their pair-bond against females that are potential mates for the male but sexual rivals for the females. We experimentally exposed breeding pairs of convict cichlids to conspecific females that differed in their reproductive state, advertised via conspicuous ornamentation. We found parental females responded aggressively to reproductive females and that parental males also behaved aggressively, particularly when mated to smaller females. These results suggest cooperation, not conflict, between parents to address potential pair-bond threats. Abstract: In many monogamous species, females behave aggressively toward other females, as they may threaten their exclusive access to paternal resources. However, in species with a high degree of breeding asynchrony not all females are true reproductive rivals. Female ornamentation that advertises sexual receptivity is a possible mechanism whereby parental females could assess the potential threat of rival females and attack only those which could challenge their mating status. Convict cichlids ( Amatitlania siquia ) are sexually dichromatic, monogamous fish that exhibit biparental care. Females develop gold ventral coloration when reproductively receptive and actively court males. We presented breeding pairs of convict cichlids with confined conspecific females to investigate whether parental response was affected by the intruder's reproductive status. We also investigated whether differences in partner quality within breeding pairs mediated the response to intruders, as mate quality influences both intra- and intersexual dynamics in many monogamous species. We found parental females responded more aggressively to reproductive intruders and that parental females mated to high quality males decreased the aggression they directed at general brood predators during the reproductive intruder presentation. Contrary to our predictions, we also found that males behaved aggressively toward reproductive intruders, particularly when paired with small females. Our results indicate that both parents engage in pair-bond defense and that differences in partner quality determine the level of aggression directed at extra-pair reproductive females. These findings suggest that when biparental care greatly increases offspring survival, reproductive success for both sexes may be maximized by cooperation and coordination, rather than conflict.